Modern approaches to social and hygienic monitoring of the health status of drivers of public transport - Babienko, V.V.; Gwantzeladze, C.R.; Sidorenko, S.G. (Актуальні проблеми транспортної медицини, 2015)
The aim of the study was to develop a system of social and hygienic monitoring of the health status of drivers of shuttle buses. The research was performed during the 2009-2014. Working conditions of drivers of shuttle buseswere evaluated. The assessment of the health status of shuttle buses drivers using objective methods of clinical and physiological, psycho-physiological and laboratory research was conducted. There was shown that existing system of pretrip and afterinspection is imperfect, run formally and requires improvement. There was developed database which includes records about health conditions and risk factors of occupational environment.The developed integrated system of social-hygienic monitoring is discussed as able to reduce car accidents and improve drivers’ health.